POLICY IMPLEMENTATION OF SUPPORT CARE AND TREATMENT SERVICES FOR HUMAN IMMUNODEFICIENCY VIRUS PATIENTS AT ANTANG HEALTH CENTER IN MAKASSAR - Suryadarma, Andi Tenri Olle; Fattah, Sulaeman; Kamariah, Najmi (Jurnal Administrasi Negara, 2023)
Makassar City is in first place with the largest number of people living with HIV in South Sulawesi. To prevent transmission from becoming more widespread, one way is done by the government by establishing HIV/AIDS services, also called Support Care and Treatment Services (PDP). This study aims to find out how the implementation of Support and Treatment Care (PDP) services for HIV patients at the Antang Health Center in Makassar City went. This research is descriptive-qualitative research. The results showed that the implementation of PDP services at the Antang Health Center in terms of human resources had already formed a PDP service working group team. In terms of services and activities, the empowerment of HIV patients has been carried out well. For the aspect of drugs and laboratory facilities, namely the availability of sufficient laboratory equipment and facilities, the availability of drugs can be fulfilled even though there has been a shortage of ARV drugs, but solutions can still be found to overcome these deficiencies. It is necessary to increase human resources, provide PDP service rooms, and arrange the flow of ARV drugs from the local Health Office.